قائمة التدفقات النقدية في تقييم السيولة والعسر المالي دراسة حالة مؤسسة عويمر الوادي بالرقيبة خلال فترة( 2021-2022-2023) IAS7دور - صابر طويل; تواوه عيسى; هارون الرشيد ين عمر (university of eloued جامعة الوادي, 2025)
"تهدف هذه الدراسة الى ابراز دور المعيار المحاسبي الدولي رقم 7 قائمة التدفقات النقدية في تقييم السيولة والعسر المالي وتعبر قائمة التدفقات عن المدخلات والمخرجات النقدية لمؤسسة وتهدف الى توفير المعلومات لمستخدمي القوائم المالية حول التغيرات الناتجة في النقدية, وتنقسم هذه القائمة الى ثلاث انشطة رئيسية وهيا: تشغيلية ,استثمارية ,تمويلية، وقد نص عن المعيار على اعدادها وفق طريقتين المباشرة وغير المباشرة . ومن أهم الأغراض التي تخدمها قائمة التدفقات النقدية قدرتها في تقييم السيولة و العسر المالي للمؤسسة لأنها توفر معلومات مفيدة لكل من الإدارة ومستخدمي القوائم المالية، وتعتبر وسيلة للتعرف على درجة السيولة التي تتمتع بها المؤسسة ومرونتها المالية ودرجة المخاطر التي تصاحب تدفقاتها. وبعد القيام بالدراسة الميدانية في مؤسسة عويمر لتغذية الانعام و الدواجن –بالوادي – تم التوصل إلى جملة من النتائج أهمها: أن قائمة التدفقات النقدية من أهم أساليب التحليل المالي تساعد المؤسسة في التعرف أكثر على وضعها المالي، و تسمح بحساب مجموعة من المؤشرات المالية المهمة لتقييم السيولة، تقييم العسر المالي, والتي تمكنها من الاستمرار قبل افلاسها . "This study aims to highlight the role of International Accounting Standard No. 7 (IAS 7), the Statement of Cash Flows, in assessing liquidity and financial distress. The cash flow statement represents an organization's cash inflows and outflows and aims to provide information to financial statement users about the resulting changes in cash and cash equivalents. It is divided into three main activities: operating, investing, and financing. The standard stipulates that this statement be prepared using either the direct or indirect method. One of the most important purposes served by the cash flow statement is its ability to assess an organization's liquidity and financial condition, as it provides useful information to both management and users of the financial statements. It serves as a tool for identifying an organization’s level of liquidity, its financial flexibility, and the degree of risk associated with its cash flows. After conducting a field study at the Awimer Livestock and Poultry Feeding Company in El Oued, several findings were reached, the most important of which are: The cash flow statement is one of the most important tools of financial analysis and helps the organization better understand its financial position. The information provided by the cash flow statement allows for the calculation of a set of significant financial indicators for assessing the organization’s status, including liquidity assessment indicators and financial distress indicators.
ماستر
Keywords: قائمة التدفقات النقدية،; تقييم السيولة ،; تقييم العسر المالي; Keywords: Cash flow statement; liquidity assessment; financial distress assessment.